Successful online learning factors in COVID-19 era: Study of Islamic higher education in West Papua, Indonesia - Agus Yudiawan; Budi Sunarso; Suharmoko Suharmoko; Fatma Sari; Ahmadi Ahmadi (International Journal of Evaluation and Research in Education (IJERE), 2021)
This study aimed to map and tests the factors that influence online learning success in the COVID-19 era in Islamic Religious Higher Education in the West Papua region. Factors to be analyzed are student characteristics, internal motivation, instructor characteristics, quality of institutions and services, infrastructure and system quality, quality of courses and information, online learning environment. The sample size obtained from the Slovin formula was 302 students. Data collected through surveys by distributing questionnaires. Analysis of the regression model used to carry out data analysis. The results showed that the seven factors tested influenced online learning success in the COVID-19 era, with varying significance. Infrastructure and system quality are the most dominant influences (94.2%), while institutions' variety and services have no significant impact (6.3%). The conclusion is that the seven factors can be used to determine the success of online learning in the COVID-19 era in Islamic Religious Higher Education in the West Papua region.